Stigma, Stigmata: Reforming the Sex Discrimination Act to Account for Menstruation as a Protected Characteristic - Liam A Holt (Bond Law Review)
This article argues that the Australian _Sex Discrimination Act 1984_ (Cth) (‘_SDA_’), as Australia’s primary source of sex and gender-based protections, fails to protect people who menstruate from discrimination. As the _SDA_ currently neglects to mention menstruation, people who menstruate cannot directly access remedies for menstrual discrimination. The harms of this are worsened by structural problems within the Australian approach to discrimination law, including in the formation of the comparator – as the experience of menstruation lacks a clear analogue. Similar issues regarding menstruation discrimination are present, and likely to become more prominent, in other jurisdictions in coming years.